y+6=-7(x+5)

Simple and best practice solution for y+6=-7(x+5) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for y+6=-7(x+5) equation:


Simplifying
y + 6 = -7(x + 5)

Reorder the terms:
6 + y = -7(x + 5)

Reorder the terms:
6 + y = -7(5 + x)
6 + y = (5 * -7 + x * -7)
6 + y = (-35 + -7x)

Solving
6 + y = -35 + -7x

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-6' to each side of the equation.
6 + -6 + y = -35 + -6 + -7x

Combine like terms: 6 + -6 = 0
0 + y = -35 + -6 + -7x
y = -35 + -6 + -7x

Combine like terms: -35 + -6 = -41
y = -41 + -7x

Simplifying
y = -41 + -7x

See similar equations:

| (18-8x)/4x | | -11=x-5-1 | | 2y+4x-3w=19 | | -4x+68=0 | | 15-1(5m-4)=34 | | (x+3)(x+4)(2)=0 | | 3/4×2×12=j | | -38-12x=-8x+18 | | 5x^2-18x+8=0 | | .25=s-5 | | 5x^2-18x+9x=0 | | -7/5b=21 | | 7-7/5b=21 | | 7+x+1=360 | | X+x+1.25=4.75 | | 9/x-2/3=0 | | k+6+2=6 | | =32x+15000 | | h=-16t^2-24+100 | | 3x+4y=500 | | 0.5(x+2)=0.4(2x-2) | | 12-6r=3r+1 | | (1/4h | | 4n+4=36whatsn | | 24xy-8y+18x-6=0 | | T/-8=-7 | | 6x+1.5=0x+2 | | 24+ln(x)=19 | | -1x+5=40 | | 10/4=4K/9 | | -38-12x=-8x+16 | | y^2+14y-36=0 |

Equations solver categories